2013
DOI: 10.1155/2013/102741
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of Hesperidin, a Plant Flavanone, on Rotenone-Induced Oxidative Stress and Apoptosis in a Cellular Model for Parkinson’s Disease

Abstract: Rotenone a widely used pesticide that inhibits mitochondrial complex I has been used to investigate the pathobiology of PD both in vitro and in vivo. Studies have shown that the neurotoxicity of rotenone may be related to its ability to generate reactive oxygen species (ROS), leading to neuronal apoptosis. The current study was carried out to investigate the neuroprotective effects of hesperidin, a citrus fruit flavanol, against rotenone-induced apoptosis in human neuroblastoma SK-N-SH cells. We assessed cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
74
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(90 citation statements)
references
References 49 publications
6
74
0
2
Order By: Relevance
“…These results were parallel to those obtained by Tamilselvam et al [43] in vitro and Zaitone et al [23] in vivo. Current results could be explained by the high lipophilic affintity of rotenone that enable it to cross blood brain barrier.…”
Section: Discussionsupporting
confidence: 91%
“…These results were parallel to those obtained by Tamilselvam et al [43] in vitro and Zaitone et al [23] in vivo. Current results could be explained by the high lipophilic affintity of rotenone that enable it to cross blood brain barrier.…”
Section: Discussionsupporting
confidence: 91%
“…The pesticide rotenone is a known inducer of ROS, and exposure to rotenone results in cell death (Tamilselvam et al, 2013). We conducted ROS assays with DCF and DCF-AG to determine their ROS activity.…”
Section: Mechanisms Of Toxicity Caused By Diclofenac Acyl Glucuronidementioning
confidence: 99%
“…The development and progress of the disease mainly depends on age, and approximately 1% of the older population (Ͼ60 yr) in industrialized countries are affected by PD (41). An increasing number of studies have suggested that numerous mechanisms, including mitochondrial defects, oxidative stress, dysimmunity, heredity, and cell apoptosis, have been implicated in the pathogenesis of PD (22,24,46,48). However, the precise mechanism underlying the pathogenesis of PD remains poorly understood, hampering the development of efficient treatments for PD.…”
mentioning
confidence: 99%